Physical rehabilitation: realities of today - Oliinyk, M. O.; Олійник, Михайло Олександрович (My University, 2023)
Physical rehabilitation is a set of measures that contribute to the restoration of full body functions and are used at certain stages of treatment. This is a set of physical exercises that contribute to improving health, physical condition and working capacity. It occupies a leading place in the complex of rehabilitation measures and is distinguished by the wide use of physical culture tools.
Keywords: physical rehabilitation; exercises; adaptation; dysfunctions; treatment